Legal Framework and Innovation of Sharia Deed-Making Techniques in the Digitalization of Notary Services in Indonesia - Maman Sudirman (JURNAL AKTA, 2025)
This study examines the urgency, challenges, and innovation models for digital-based sharia deed creation in Indonesia by examining its relationship with the Quran, Sunnah, fatwas of the National Ulema Council (DSN-MUI), the Notary Law (UUJN), and the Information and Electronic Transactions Law (UU ITE). The research method used is normative legal research with a legislative approach, which reviews relevant laws and regulations, such as the Criminal Code, the Law on the Status of Notaries (Law Number 2 of 2014), Law Number  1 of 2024 as the Second Amendment to Law No. 11 of 2008 concerning Information and Electronic Transactions, Government Regulation Number  71 of 2019, and the DSN-MUI fatwa on muamalah contracts, conceptual approaches, and literature. The results of the study indicate that the application of digital technology in the creation of sharia deeds requires regulatory adjustments to align with the provisions of the UUJN and utilize the legitimacy of documents and electronic signatures as regulated in the ITE Law. Regulatory integration, increased digital literacy, and strengthened technological infrastructure are necessary to ensure that digital Sharia deeds have the same legal force as conventional deeds and comply with Sharia principles.